2012
DOI: 10.1111/cmi.12071
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor complex AP-1 mediates inflammation initiated byChlamydia pneumoniaeinfection

Abstract: Summary Chlamydia pneumoniae is responsible for a high prevalence of respiratory infections worldwide and has been implicated in atherosclerosis. Inflammation is regulated by transcription factor (TF) networks. Yet, the core TF network triggered by chlamydiae remains largely unknown. Primary human coronary artery endothelial cells were mock-infected or infected with C. pneumoniae to generate human transcriptome data throughout the chlamydial developmental cycle. Using systems network analysis, the predominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 69 publications
2
51
0
2
Order By: Relevance
“…1E, right). This is consistent with AP-1 and ETS roles in mediating the inflammatory response, as both families have been implicated in responding to tumor necrosis factor alpha signaling and have been reported to induce cytokine expression in endothelial and epidermal tissues (28)(29)(30)(31)(32). At genomic regions that lose enhancer chromatin structure upon inflammation, colonic developmental transcription factor motifs predominated (KLF, HNF4, and HNF1), suggesting that these regions lose their transcription factor occupancy during colitis (33)(34)(35)(36)(37).…”
Section: Resultssupporting
confidence: 75%
“…1E, right). This is consistent with AP-1 and ETS roles in mediating the inflammatory response, as both families have been implicated in responding to tumor necrosis factor alpha signaling and have been reported to induce cytokine expression in endothelial and epidermal tissues (28)(29)(30)(31)(32). At genomic regions that lose enhancer chromatin structure upon inflammation, colonic developmental transcription factor motifs predominated (KLF, HNF4, and HNF1), suggesting that these regions lose their transcription factor occupancy during colitis (33)(34)(35)(36)(37).…”
Section: Resultssupporting
confidence: 75%
“…The AP-1 complex is targeted by several bacterial pathogens to alter cellular survival or prevent inflammation and cytokine production, with some pathogens preventing activation and some inducing activation of upstream host signaling cascades (Alto and Orth, 2012). Interestingly, a recent report using C. pneumoniae suggested that AP-1 activation is responsible for inflammation seen in vivo (Wang et al, 2012). While the effect of AP-1 on inflammation during infection in vivo remains to be confirmed for C. trachomatis , these data together suggest that finely tuned AP-1 signaling is required for robust intracellular growth.…”
Section: Discussionmentioning
confidence: 99%
“…2,15,16 AP-1 protein is primarily regulated at the level of both Jun and Fos gene transcription involving mitogen-activated protein kinases (MAPKs) pathways and by post-translational modification via phosphorylation and dephosphorylation. 15 …”
Section: Ap-1 Signaling Pathwaysmentioning
confidence: 99%